2011
DOI: 10.3961/jpmph.2011.44.6.260
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness is Associated With Diabetic Retinopathy in Korean Type 2 Diabetic Patients

Abstract: ObjectivesWe evaluated the association between common carotid artery intima-media thickness (CCA-IMT), brachial-ankle pulse wave velocity (baPWV), carotid plaque, and peripheral arterial disease (PAD) as indicators of macroangiopathy and diabetic retinopathy as an indicator of microangiopathy in type 2 diabetic patients.MethodsWe analyzed 605 type 2 diabetic patients registered at a public health center in Korea. Following overnight fasting, venous blood and urine samples were collected and analyzed. The CCA-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…These associations are suggestive of PWV being related to vascular dysfunction (20) and large artery alterations, thereby possibly engaging in the development of kidney impairment (21). Arterial stiffness also is associated with autonomic neuropathy in type 1 diabetes (22,23) and retinopathy in type 2 diabetes (24), further illustrating the association between arterial stiffness and microvascular disease.…”
mentioning
confidence: 90%
“…These associations are suggestive of PWV being related to vascular dysfunction (20) and large artery alterations, thereby possibly engaging in the development of kidney impairment (21). Arterial stiffness also is associated with autonomic neuropathy in type 1 diabetes (22,23) and retinopathy in type 2 diabetes (24), further illustrating the association between arterial stiffness and microvascular disease.…”
mentioning
confidence: 90%
“…In addition, microangiopathy is a strong predictor of the development of the more serious long-term complications of diabetes such as blindness, end-stage renal disease, amputation [5], and cardiovascular disease [6]. Previous studies have shown that PWV, a marker of arterial stiffness, is associated with the presence of diabetic retinopathy [711]. …”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a lack of a consensus amongstr both ophthalmologists and physicians to apply these risk factors to assess the onset of PAD and CVD in patients with DR. Additionally, an abnormal ABI value and the duplex ultrasonograph can help to confirm the association between PAD and DR [21,22]. On the one hand, ophthalmologists tend to focus on the diagnosis and treatment of DR, but ignore the importance of these risk factors in the assessment of PAD and CVD.…”
mentioning
confidence: 99%